HTLV-1-related adult T-cell leukemia/lymphoma: insights in early detection and management. Issue 5 (25th September 2022) - Wolf, Sonia; Vercruyssen, Marie; Cook, Lucy
Abstract : Purpose of review: Adult T-cell leukemia-lymphoma (ATL) is an aggressive mature T-cell malignancy that arises in approximately 5% of carriers of human T-lymphotropic virus type 1 (HTLV-1), but this risk is not random among carriers. We describe recent advance in pathogenesis, risk factors and for early detection of ATL. Recent findings: Unraveling ATL molecular genetics has shed light on pathogenesis and provides insights into novel therapeutic targets. Moreover, an important step in improving outcomes is identifying asymptomatic carriers who are at high risk of progression to ATL, which has traditionally relied on quantifying the proviral load (PVL). This can be done by quantifying oligoclonality- and in particular the expanded clone- with molecular and flow cytometric techniques, that can be applied to a clinical setting. Studies using these methods have shown that carriers with oligoclonal populations are at an increased risk of transformation, beyond that that predicted by PVL alone. Summary: There is an urgent unmet need for developing novel therapies in ATL in order to improve survival. Recent advances in the molecular and epigenetic landscape of ATL, and the early detection of disease offer the potential to intervene early, before disease becomes aggressive, and to offer tailored therapeutic strategies.